Measles infection causing Bacillus Calmette-Guérin reactivation: a case report - Sobana Muthuvelu; Kev Shiau-Chong Lim; Ling-Yin Huang; Shi-Tying Chin; Anand Mohan (BMC, 2019)
Abstract Background Reactivation of the Bacillus Calmette-Guérin (BCG), manifesting as erythema, induration, ulceration or crust formation at a previous BCG inoculation site, is a common and highly specific feature of Kawasaki disease (KD). We report the unusual finding of BCG reactivation in an infant with laboratory-confirmed measles. Case presentation A previously healthy 7-month old infant presented initially with fever, cough and coryza, and subsequently developed Koplik's spots followed by a typical morbilliform skin rash. There was significant contact history with a household relative who had recently been diagnosed with measles. On examination, a 2.5 cm area of erythema and induration was seen at the previous BCG inoculation site, in addition to the widespread maculopapular rash. No other clinical features of KD were present. Measles virus was isolated from the throat swab and measles antibodies (IgM) were present in the serum. The patient recovered completely with oral vitamin A and supportive therapy, and had normal echocardiography examination on follow up. Conclusions This case report highlights the rare finding of BCG reactivation in a child with confirmed measles infection, and suggests that this clinical manifestation may occasionally occur in children with infections or conditions other than KD.